2013
DOI: 10.1016/j.neuroimage.2013.06.076
|View full text |Cite
|
Sign up to set email alerts
|

Excitability modulation of the motor system induced by transcranial direct current stimulation: A multimodal approach

Abstract: Anodal and cathodal transcranial direct current stimulations (tDCS) are both established techniques to induce cortical excitability changes. Typically, in the human motor system, such cortical modulations are inferred through changes in the amplitude of the motor evoked potentials (MEPs). However, it is now possible to directly evaluate tDCS-induced changes at the cortical level by recording the transcranial magnetic stimulation evoked potentials (TEPs) using electroencephalography (EEG). The present study inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
104
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(116 citation statements)
references
References 74 publications
(99 reference statements)
12
104
0
Order By: Relevance
“…In a recent study (Pellicciari, Brignani, & Miniussi, 2013), an increment of both cortical and corticospinal measures, namely TEPs and MEPs, was found after anodal tDCS over M1, suggesting that tDCS alone might raise cortical reactivity underneath the electrode and in the contralateral homologue area. However, to definitely exclude any potential effect of the TMS-tDCS combination, we ran a control experiment in which no TMS was applied during the tDCS stimulation.…”
Section: Discussionmentioning
confidence: 92%
“…In a recent study (Pellicciari, Brignani, & Miniussi, 2013), an increment of both cortical and corticospinal measures, namely TEPs and MEPs, was found after anodal tDCS over M1, suggesting that tDCS alone might raise cortical reactivity underneath the electrode and in the contralateral homologue area. However, to definitely exclude any potential effect of the TMS-tDCS combination, we ran a control experiment in which no TMS was applied during the tDCS stimulation.…”
Section: Discussionmentioning
confidence: 92%
“…They showed that the motor cortical area ipsilateral to the stimulation responded within 3-7 ms, while contralateral motor areas responded with longer latencies (17-28 ms) (Ilmoniemi et al, 1997;Komssi et al, 2002). More recent studies demonstrated that the amplitude of early components of motor cortex TEPs undergoes significant changes after the application of rTMS or transcranial Direct Current Stimulation (tDCS), two brain stimulation techniques that are thought to modulate synaptic strength and cortical excitability (Esser et al, 2006;Pellicciari et al, 2013;Veniero et al, 2012Veniero et al, , 2010. Finally, it has been shown that the peak-to-peak amplitude of the N15-P30 complex (composed by a negative deflection at 15 ms followed by a positive deflection at 30 ms) correlated with MEP amplitude on a single-trial basis (MĂ€ki and Ilmoniemi, 2010) and was strongly affected by the TMS coil orientation (Bonato et al, 2006).…”
Section: Early Components Of Motor Cortex Tepsmentioning
confidence: 99%
“…Anodal stimulation increases cortical excitability, whereas cathodal stimulation decreases it. Functional neuroimaging and transcranial magnetic stimulation (TMS) studies report that tDCS can modulate motor cortex excitability in normal patients [16,18,19]. However, little is known about this topic in stroke patients, and knowledge regarding the mechanisms of motor recovery following tDCS remains limited in stroke patients.…”
Section: Introductionmentioning
confidence: 99%